Pelatihan Produk Turunan Minyak Sereh Program Kosabangsa Unversitas La Tansa Mashiro - Universitas Andalas - Yumhi; Eka Candra Lina; Yusup Junaedi; Egi Adha Juniawan; Prima Fithri; Hasmiandy Hamid (Warta Pengabdian Andalas, 2024)
This training is important in utilizing the citronella owned by the farmer group with a land area of ​​approximately 4 Ha. So far, it has only been processed into oil with poor quality because it has higher water content. The oil results are sold by the kilo at a low selling price. In addition, the youth organization in Cibarani Village only has activities during national holidays. Hence, they lack the skills to optimize the potential of their area, which is rich in natural resources. The method used in this training is training and direct practice in making derivative products such as bar soap, dishwashing, hand soap, and detergent based on citronella. The training results are increased knowledge and skills of the farmer group and youth organization of Cibarani Village in optimizing citronella through derivative products with higher selling value.